2007
DOI: 10.1177/0044118x06296637
|View full text |Cite
|
Sign up to set email alerts
|

Matched or Mismatched Environments? The Relationship of Family and School Differentiation to Adolescents' Psychosocial Adjustment

Abstract: This study applies the family-systems concept of differentiation (the balance of autonomy-granting and connectedness) to another primary system of adolescent development—school. This study assessed the relationships among levels of family and school differentiation to the externalizing and internalizing behaviors, peer group membership, and academic achievement of 693 middle and high school students. High levels of family and school differentiation were correlated with all measures of well-being. Individuals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
0
13
0
3
Order By: Relevance
“…Horizontalius santykius, vyraujančius tarp bendraamžių grupių narių, nulemia panaši jų gyvenimiška patirtis ir socialinė galia. Vis dėlto grupė, būdama labai reikšminga paauglio gyvenime, turi gana didelę įtaką keičiant paauglio nuostatas ir elgseną (Cotterell, 1996;Battisch et al, 1997;Eccles, Roesser, 1999;Roesser et al, 2001;Barber, Olsen, 2004;Virbalienė, 2004;Giovanna et al, 2005;Lohman et al, 2007). Socialinės adaptacijos sėkmė naujoje gimnazijos klasėje taip pat atsispindi gimnazistų tarpasmeniniuose santykiuose su mokiniais, mokytojais ir jų tėvais Langenkamp, 2004;Poderienė, 2004).…”
unclassified
“…Horizontalius santykius, vyraujančius tarp bendraamžių grupių narių, nulemia panaši jų gyvenimiška patirtis ir socialinė galia. Vis dėlto grupė, būdama labai reikšminga paauglio gyvenime, turi gana didelę įtaką keičiant paauglio nuostatas ir elgseną (Cotterell, 1996;Battisch et al, 1997;Eccles, Roesser, 1999;Roesser et al, 2001;Barber, Olsen, 2004;Virbalienė, 2004;Giovanna et al, 2005;Lohman et al, 2007). Socialinės adaptacijos sėkmė naujoje gimnazijos klasėje taip pat atsispindi gimnazistų tarpasmeniniuose santykiuose su mokiniais, mokytojais ir jų tėvais Langenkamp, 2004;Poderienė, 2004).…”
unclassified
“…Thus, it is hypothesized that the influence of bridging social capital on future civic involvement should be the most optimal when adolescents are embedded in and have experiences of neighborhoods, families, and schools with high levels of social capital (Bronfenbrenner & Morris, 1998;Lohman et al, 2007). Specifically, it is hypothesized that the presence of high neighborhood assets will positively contribute to the development of family social capital during adolescence, which in turn will contribute to the development of the adolescent's school social capital.…”
Section: Bridging Capital: Linking Families Schools and Neighborhoodsmentioning
confidence: 99%
“…Congruency within a mesosystem is related to the degree of consistency or agreement in the contexts; in other words, environmental congruency examines whether multiple contexts complement each other to influence an adolescent's development (Eccles, 2004;Gutman & Eccles, 2007;Roberts & Robins, 2004). Indeed, greater consensus between environments has been shown to yield better outcomes (Brand & Felner, 1996;Lohman, Kaura, & Newman, 2007).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Extending the bioecological model, the influence of early perceived supportive control of the community and family on adolescent after-school involvement should be the most optimal when adolescents are surrounded by contexts matched in values, particularly support, trust and cohesion (Brand & Felner, 1996;Bronfenbrenner, 1989;Eccles, 1993;Lohman, Kaura & Newman, 2007;Roberts & Robins, 2004). As Anderson et al (2007) found, having a greater number of external supports and opportunities was associated with an increase in prosocial outcomes and a decrease in the probability of risk behaviors.…”
Section: Environmental Congruence: the Community And Family Mesosystemmentioning
confidence: 99%
See 1 more Smart Citation